Association between maternal shift work during pregnancy child overweight and metabolic outcomes in early childhood - Liao, Che-Wei; Wei, Chih-Fu; Chen, Mei-Huei; Hsieh, Wu-Shiun; Lin, Ching-Chun; Chen, Pau-Chung (Frontiers in Public Health, 2022)
Background: Previous studies found that maternal shift-work during pregnancy was associated with many reproductive hazards, including small for gestational age, preterm birth, stillbirth, and neurodevelopmental impairment. Some studies also showed that these children are more likely to become overweight in early childhood. However, the association with metabolic factors, such as insulin resistance, and dyslipidemia, was less studied. Hence, we aimed to understand better the relationship between maternal shift-work during pregnancy and the risk of child overweight, and metabolic disorders. Confounding factors were also discussed, including diet, exercise, and demographical factors. Methods: We enrolled pregnant women before delivery into Taiwan Birth Panel Study II, TBPS II in 2011-2012, and followed the children of these participants in 2018. The study is to investigate prenatal and postnatal factors on infant and early childhood health. During the follow-up in 2018, we checked children’s demographic data, obtained blood specimens, and checked their blood sugar, blood insulin, and lipid profile. Structured questionnaires were used to evaluate demographic data. multivariable linear and logistic regressions were used to examine the associations between maternal shift-work during pregnancy and child overweight, metabolic disorders, such as HOMA-IR, and lipid profiles. Results: In this study, 407 mother-children pairs with different work shifts (350 day-workers and 57 shift workers) were included, and a subpopulation without underweight children was also created (290 day-workers, 47 shift workers). Shift work during pregnancy was associated with a higher Homeostasis Model Assessment-Insulin Resistance index (HOMA-IR) and a higher odds ratio for overweight in children of shift work during pregnancy after adjusted. The findings were attenuated if we investigated the effect of shift work before pregnancy. Conclusions: Our study suggested that maternal shift work during pregnancy was associated with child overweight and insulin resistance in early childhood.